(untitled) (Global Conference on Medical and Health Sciences, 2026)
Acute kidney injury (AKI) remains a pressing clinical problem in intensive care units worldwide due to its high incidence and significant impact on patient morbidity and mortality. Despite advances in critical care, AKI continues to pose diagnostic and therapeutic challenges, particularly in its early stages when intervention can most effectively improve outcomes.